BASIC PRINCIPLES OF VOCAL PEDAGOGY - Rasulova Saida Sabirovna (Galaxy International Interdisciplinary Research Journal, 2022)
This article discusses the history of Uzbek folk music, the main principles of vocal pedagogy.